Long term economic relationships from cointegration maps - Vicente, Renato; Pereira, Carlos de B.; Leite, Vitor Barbanti Pereira; Caticha, Nestor (Elsevier B.V., 2007)
We employ the Bayesian framework to define a cointegration measure aimed to represent long term relationships between time series. For visualization of these relationships we introduce a dissimilarity matrix and a map based on the sorting points into neighborhoods (SPIN) technique, which has been previously used to analyze large data sets from DNA arrays. We exemplify the technique in three data sets: US interest rates (USIR), monthly inflation rates and gross domestic product (GDP) growth rates. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: complex systems; econophysics; cointegration; clustering; Bayesian inference